WORKING MOTHER AND FAMILY ECONOMY RESILIENCE IN THE COVID-19 ERA: EVIDENCE FROM INDONESIA - Azizah, Siti Nur; Salam, Annisa Nur (Jurnal Ilmu Keluarga dan Konsumen, 2021)
Covid-19 pandemic, which occurred in early 2020, has resulted in more than 50 percent of households experiencing financial difficulties, especially those who rely on personal businesses. This study aims to analyze the effect of working mothers on family economic resilience during the Covid-19 pandemic. This study obtained the primary data by distributing questionnaires to 173 respondents using the purposive sampling technique. The approach used is quantitative with Ordinary Least Square (OLS) as the data analysis method. The dependent variable is family economic resilience, and the independent variable is female workers. The results showed that working women could support and contribute to their households in helping meet the daily needs of their families. Thus, working mothers have a positive effect on household economic resilience during the Covid-19 pandemic. For this reason, during the Covid-19 period, a wife's role is needed to contribute to the family economy so that the family's economic resilience remains stable. Furthermore, this research revealed the importance of the government's roles and stakeholders to provide facilities such as working capital for women, availability of employment opportunities for women, and work regulations that support women in balancing their dual roles.